2017
DOI: 10.1038/s41598-017-14669-2
|View full text |Cite
|
Sign up to set email alerts
|

KRAS mutation and primary tumor location do not affect efficacy of bevacizumab-containing chemotherapy in stagae IV colorectal cancer patients

Abstract: This study aims to investigate the efficacy of bevacizumab-combined chemotherapy (BCC) in Chinese stage IV colorectal cancer (CRC), and analyze the relationship between clinicopathological features with survival. Patients with stage IV CRC treated with BCC were analyzed retrospectively. 217 metastatic CRC (mCRC) patients were collected, out of which79 were right-sided CRCs and 138 were left-sided ones. Patients with Eastern Cooperative Oncology Group (ECOG) performance status ≤2, single agent chemotherapy, poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…A posthoc analysis of this trial suggested a benefit from bevacizumab in addition to chemotherapy independently of primary tumor localization regarding the reported endpoint progression-free survival (28). Similar results were reported in a prospective trial on a Chinese cohort (29).…”
Section: Discussionsupporting
confidence: 81%
“…A posthoc analysis of this trial suggested a benefit from bevacizumab in addition to chemotherapy independently of primary tumor localization regarding the reported endpoint progression-free survival (28). Similar results were reported in a prospective trial on a Chinese cohort (29).…”
Section: Discussionsupporting
confidence: 81%
“…To the best of our knowledge, the influence of ECOG score on the prognosis of patients was confirmed in a previous study, which suggested that the higher the score, the worse the prognosis. 26 Results of the Cox regression analysis in our study indicated that patients with ECOG 1-2 scores were associated with worse DFS. On the other hand, in view of the poor adherence to drug administration among patients with NSCLC in the real world, the median course of adjuvant chemotherapy in our study was three (range one to five), and the insufficient adjuvant chemotherapy failed to reduce the recurrence risk of patients with NSCLC, in accordance with proved a previous study.…”
Section: Discussionmentioning
confidence: 47%
“…Due to this association, CDKN2A alterations were not considered as a new independent marker for bevacizumab treatment outcome. Results from the literature do not show survival differences in bevacizumab-treated CRC patients according to KRAS mutation status [10,11,17]. Similarly, TP53 mutation status was not associated with survival in bevacizumab-treated patients [11].…”
Section: Discussionmentioning
confidence: 99%